Investigasi Difusi pada Sistem Urinari untuk Gangguan Fungsi Ginjal Model Empat Kompartemen menggunakan Metode Monte Carlo - Jovi Yuzzer Budiman; Jodelin Muninggar; Adita Sutresno (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
Kidney is a pair of organ in our urinary system that function to filter blood and urine establishment through filtration, reabsorption and secretion process.Formation of urine is done through one of processes, named tubular reabsorption. This process is a process of diffusion, passively and facilitated. The process happens in tubular reabsorption in kidney can be simulated by using Monte Carlo Cell simulation. Making model of 4 compartments consist of blood vessel, 2 kidneys with one kidney experiencing decreased function of kidney and bladder. Two kidney compartments with one of it experiencing decreased function affect the diffusion process that happens in substance reabsorption process in kidney.The purpose of this research is to study the diffusion process which happens in kidney by selecting several fixed variable and indicators which will be inspected by using Monte Carlo Cell simulation. The use of Monte Carlo Cell simulation enable to try any probabilities that occur in diffusion process of filtration, reabsorption and secretion process in kidney. The result of this research shows that the fewer number of molecules, the slower the molecular displacement and also the fewer number of surface molecules, the slower the molecular displacements.